Mentoring for women and underrepresented minority faculty and students: experience at two institutions of higher education. - Kosoko-Lasaki, Omofolasade (National Medical Association, 2006)
Women and minority faculty and students are seriously underrepresented in university and academic healthcare institutions. The role of mentoring has been identified as one of the significant factors in addressing this underrepresentation. We have described the mentoring efforts at two institutions of higher learning in assisting women and minority students and faculty in being accomplished in their academic pursuits. One-hundred-thirty students and >50 women and minority faculty have participated in the mentoring programs described. The number of participants has increased dramatically over the years and continues to evolve positively. These programs appear to be quite successful in the short term. Further evaluation of measurable outcomes will be necessary to fully determine their true impact. The mentoring models for women and underrepresented minority faculty and students at Creighton University Health Sciences Schools and Wake Forest University School of Medicine will serve as a guide for other Health Sciences Schools.